FRI0059 The efficacy and safety of pegylated recombinant methionyl human soluble tumour necrosis factor receptor type i (peg stnf-ri; p55) in a randomised, placebo-controlled, clinical study of patients with rheumatoid arthritis (ra). (1st June 2001) - Schiff, M; Furst, D; Fleischmann, R; Macri, M; Joh, T; Edwards, CK; Davis, MW
Abstract : Background: Objectives: PEG sTNF-RI was administered weekly for 12 weeks at 400 or 800 μg/kg vs placebo to assess efficacy and safety for the treatment of patients with RA. Methods: Subjects were randomised at 15 U. S. centres to receive PEG sTNF-RI or placebo (1:1:1). Subjects with disease duration of at least 6 months with > = 10 swollen joints and > = 12 tender/painful joints, and morning stiffness > = 45 min, C-reactive protein (CRP) > = 1.5 mg/dL, or erythrocyte sedimentation rate (ESR) > = 28 mm/hr were eligible for study. Subjects were allowed to continue most single or combination background DMARD therapies. If taking DMARDs, the doses must have been stable for 8 weeks before entry; only combination therapy involving methotrexate with sulfasalazine or hydroxychloroquine, or sulfasalazine plus hydroxychloroquine were allowed. Clinic visits occurred at baseline and weeks 1, 2, 4, 8, and 12. Study related observations consisted of efficacy assessments, physical examination, laboratory assessments, adverse events (noninfectious adverse events and infectious episodes), concomitant medications, PEG sTNF-RI antibodies, and autoantibodies. Results: A total of 195 subjects were randomised and 194 subjects received > = 1 dose of study drug. Efficacy: Subjects in the 800 μg/kg PEG sTNF-RI dose group had an ACR20 response rate of 50% which was significantly different (p = 0.005) from the placebo group (26%). TheACR20 response rate for the 400 μg/kg group was 33% (NS vs. placebo). An increasing ACR20 response rate with increasing PEG sTNF-RI dose was detected at week 12 (p = 0.017). Treatment with 800 μg/kg PEG sTNF-RI resulted in statistically significant improvements in all individual ACR components except for swollen joint counts and CRP. Safety: No deaths or malignancies were reported. Two subjects experienced serious events; neither event was judged to be related to study drug or resulted in withdrawal from the study. The incidence of infectious episodes was slightly higher in subjects receiving PEG sTNF-RI (27%) compared with subjects receiving placebo (21%). Only the incidence of injection site reactions appeared to be treatmentÓrelated; (20% PEG sTNF-RI, 10% placebo). Noninfectious adverse events that occurred more frequently in PEG sTNF-RI subjects compared with placebo included diarrhoea (8% vs. 3%), dizziness (6% vs. 3%), and nausea (6% vs. 3%). No PEG sTNF-RI treatmentÓrelated effects on laboratory variables, vital signs, or antibodies were evident. Conclusion: Weekly dosing with PEG sTNF-RI (400- or 800-μg/kg) for 12 weeks demonstrated a beneficial treatment effect in improving the signs and symptoms of subjects with RA. Treatment with PEG sTNF-RI appeared to be safe and well-tolerated. The type and incidence of adverse events was similar to those observed in clinical trials with other TNF-α inhibitors. Further patient exposure will be required to fully characterise the adverse event profile of PEG sTNF-RI in subjects with rheumatoid arthritis. Future studies will evaluate higher and more frequent dosing.